Inflation: Viewed in terms of Economic Structure, Aggregate Expenditure, Wages and Currency Value in a Review - Endah Suci Damayanti (Formosa Journal of Multidisciplinary Research, 2023)
Research objectives are to provide an overview of existing results from previous studies and provide conclusions by researchers. The research method used is a literature review that comes from existing scientific articles from various journals in the world related to variables.The results of the research in this study gave significant results with quantitative research methods and mostly used qualitative methods with the results of the researcher's perspective. Researchers highlight that the field of finance with variables written in research in this paper should use qualitative methods.